Diagnostic Evaluation of Barium Enema in Colorectal Cancer and Its Correlation with Histopathology - Gafur, Md Abdul; Tabassum, Rumana (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Colorectal cancer is common in western countries and less common in Asian countries. The aim of the study to determine the diagnostic value of barium enema in colorectal cancer. Materials and methods: A prospective study was carried out on 50 cases presented with clinical features of colorectal cancer in Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital and National Institute of Cancer Research & Hospital (NICRH) during the session July 2000 to June 2001. The male was 30 and female 20. Mean age of the male was 46 ± 10.8 years that of female was 44.5 ± 11.2 years. Results: No statistically significant difference was found between age and sex of the patients. People suffer at an earlier age in our country than western people and highest number of cases occurred at 4th and 5th decade. Males pre- dominate over females and the rectum is more involved than the colon. 96% of patients took meat and fat and one patient had a family history of colon cancer. Colorectal cancer was more (44%) in better socio-economic condition than low (4%). Constipation (70%) and per rectal bleeding (64%) were predominant symptoms and 68% cases had abnormality in per rectal examination. Out of 40 cases colonoscopy detected lesion in 33 cases, one was false positive and 7 cases were negative, of them 3 cases were false negative, 4 true negative. In 50 cases barium enema detected lesion in 42 cases, 2 were false positive. 8 cases were negative in barium enema of them 5 were false negative and 3 true negative. Histologically 45 (90%) cases proved to be adenocarcinoma, among them 4 (8%) cases were mucinous adenocarcinoma. Histologically 5 cases were negative. The sensitivity and accuracy of barium enema was 88.9% and 86% and that of colonoscopy was 91.4% and 90% respectively. Conclusion: Though colonoscopy had greater sensitivity and accuracy, it is less acceptable to the patients, high cost, not easily available, requires sedation and expertise and entire colon is not seen in 2-40% of the patient. Barium enema maybe accepted asinitial investigation in the diagnosis of clinically suspected colorectal cancer. JCMCTA 2020 ; 31 (2) : 49-53